2021
DOI: 10.3390/app112412019
|View full text |Cite
|
Sign up to set email alerts
|

Attention Mechanism-Based Convolutional Long Short-Term Memory Neural Networks to Electrocardiogram-Based Blood Pressure Estimation

Abstract: Monitoring people’s blood pressure can effectively prevent blood pressure-related diseases. Therefore, providing a convenient and comfortable approach can effectively help patients in monitoring blood pressure. In this study, an attention mechanism-based convolutional long short-term memory (LSTM) neural network is proposed to easily estimate blood pressure. To easily and comfortably estimate blood pressure, electrocardiogram (ECG) and photoplethysmography (PPG) signals are acquired. To precisely represent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The prediction results of the model on the two datasets both achieved the grade A of the BHS standard and satisfied the AAMI standard. Chuang et al [ 78 ] screened 11,000 PPG and ECG segments from 45 subjects in the MIMIC dataset and introduced an attention mechanism to the CNN-LSTM model to identify meaningful features. The results showed that combining the time and frequency domain signals of PPG and ECG could fully obtain the intrinsic characteristics of the signals, which resulted in an error (MAE ± STD) of 2.94 ± 4.65 mmHg for SBP and 2.02 ± 3.81 mmHg for DBP.…”
Section: Methodsmentioning
confidence: 99%
“…The prediction results of the model on the two datasets both achieved the grade A of the BHS standard and satisfied the AAMI standard. Chuang et al [ 78 ] screened 11,000 PPG and ECG segments from 45 subjects in the MIMIC dataset and introduced an attention mechanism to the CNN-LSTM model to identify meaningful features. The results showed that combining the time and frequency domain signals of PPG and ECG could fully obtain the intrinsic characteristics of the signals, which resulted in an error (MAE ± STD) of 2.94 ± 4.65 mmHg for SBP and 2.02 ± 3.81 mmHg for DBP.…”
Section: Methodsmentioning
confidence: 99%
“…(3) Some systems developed for non-invasive BP monitoring include photoplethysmography (PPG) optical sensors based on electron waves, a BP estimation device based on the volume compensation principle, a blood modulation magnetic signal mechanism, and a portable cuff BP sensing system. (4)(5)(6)(7)(8)(9)(10)(11) However, these devices are all in the form of stand-alone devices and are only used for BP measurement and do not include other vital signs. In addition, when some of them are used in real life, especially by specific user groups, the ideal laboratory effect cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…CAD is commonly identified and diagnosed based on different tests, such as ECG, treadmill ECG, echocardiogram (ECHO), and angiography. The intelligent systems use different neural architectures, such as the convolutional neural network CNN [11], recurrent neural network (RNN) [12], CNN with RNN [13,14], deep belief network (DBN) [3,15], and the fully-connected neural network (FC) [11] to predict electrocardiogram (ECG)-related issues, such as arrhythmia [16][17][18][19][20], atrial fibrillation (AF) [21][22][23], myocardial infarction (MI) [24,25], ST elevation [21], CAD [10,[26][27][28], etc. Tan, J.H.…”
Section: Introductionmentioning
confidence: 99%